Orientational isotopic effects in the thermal conductivity of solid CH4/CD4 solutions - Krivchikov, A.I.; Stachowiak, P.; Pisarska, E.; Jezowski, A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
The thermal conductivity of solid (CH4)1–c(CD4)c solutions with c= 0, 0.03, 0.065, 0.13, 0.22, 0.4, 0.78, and 1.0 has been measured in the region of existence of three orientational phases: disordered (phase I), partially ordered (phase II) and completely ordered (phase III). The temperature range is 1.3–30 K. It is shown that the thermal conductivity has different temperature dependences к(T) in these phases. Its value increases with the degree of the orientational order in the phase. In phase I the thermal conductivity is independent of c and weakly dependent on T. The impurity effect in к(T)is much stronger in the low-temperature part of phase II than in phase III. As the concentration c grows, the к(T) curve of phase II approaches the dependence к(T) typical of phase I. There is a hysteresis in the vicinity of the II↔III phase transition. In phase III the impurity effect in к(T) can be considered as phonon scattering at rotational defects developing due to the difference between the moments of inertia of the CH4 and CD4 molecules. The obtained dependences of thermal conductivity on temperature and concentration can be explained qualitatively assuming that the dominant mechanism of phonon scattering is connected with the interaction of phonons with the rotational motion of the molecules in all of the three orientational phases of the CH4–CD4 system.